The Presence of the Prophet in Early Modern and Contemporary Islam : Volume 1, The Prophet Between Doctrine, Literature and Arts: Historical Legacies and Their Unfolding - Gril, Denis; Sarmis, Dilek; Reichmuth, Stefan (Handbook of Oriental studies. Near and Middle East (2014), 2022)
The three-volume series titled The Presence of the Prophet in Early Modern and Contemporary Islam , is the first attempt to explore the dynamics of the representation of the Prophet Muhammad in the course of Muslim history until the present. This first collective volume outlines his figure in the early Islamic tradition, and its later transformations until recent times that were shaped by Prophet-centered piety and politics. A variety of case studies offers a unique overview of the interplay of Sunnī amd Shīʻī doctrines with literature and arts in the formation of his image. They trace the integrative and conflictual qualities of a "Prophetic culture", in which the Prophet of Islam continues his presence among the Muslim believers. Contributors Hiba Abid, Nelly Amri, Caterina Bori, Francesco Chiabotti, Rachida Chih, Adrien de Jarmy, Daniel De Smet, Mohamed Thami El Harrak, Brigitte Foulon, Denis Gril, Christiane Gruber, Tobias Heinzelmann, David Jordan, Pierre Lory, Catherine Mayeur-Jaouen, Samuela Pagani, Alexandre Papas, Michele Petrone, Stefan Reichmuth, Meryem Sebti, Dilek Sarmis, Matthieu Terrier, Jean-Jacques Thibon, Marc Toutant, Ruggiero Vimercati Sanseverino.